Assessment of environmental radioactivity in soil samples from Bartin Province, Turkey - Öge, Tuba Özdemir; Ozdemir, Firdevs Banu; Öge, Mecit; Öge, Tuba Özdemir; Öge, Mecit (Springer, 2021)
The radioactivity levels in the soil samples from Bartin Province, Turkey were determined using a HPGe detector, and the hazard parameters were calculated. The mean concentration values were measured as 6 +/- 2; 7 +/- 3; 136 +/- 15; 2 +/- 1 and 8 +/- 3 Bq kg(-1), for U-238, Th-232, K-40, Cs-137 and Ra-226, respectively. The average radium equivalent, absorbed gamma dose rate, annual effective dose equivalent, external hazard index and excess lifetime cancer risk were calculated as 26.74 Bq kg(-1), 12 +/- 3 nGy h(-1), 15 +/- 3 mu Sv y(-1), 0.1 +/- 0.02 and 0.053 +/- 0.011, respectively. Amasra district exhibited the highest radiological hazard parameters which is attributed to the mining activities. All measured and calculated values were found to remain under the limit values.
Keywords: Radioactivity Measurement; Natural Radioactivity In Soil; Gamma Measurement System; Activity Concentration